Markov–Bernstein inequalities for generalized Gegenbauer weight - Draux, André; Sadik, Mohamed; Moalla, Borhane (Applied numerical mathematics, 2011)
The Markov–Bernstein inequalities for generalized Gegenbauer weight are studied. A special basis of the vector space P n of real polynomials in one variable of degree at most equal to n is proposed. It is produced by quasi-orthogonal polynomials with respect to this generalized Gegenbauer measure. Thanks to this basis the problem to find the Markov–Bernstein constant is separated in two eigenvalue problems. The first has a classical form and we are able to give lower and upper bounds of the Markov–Bernstein constant by using the Newton method and the classical qd algorithm applied to a sequence of orthogonal polynomials. The second is a generalized eigenvalue problem with a five diagonal matrix and a tridiagonal matrix. A lower bound is obtained by using the Newton method applied to the six term recurrence relation produced by the expansion of the characteristic determinant. The asymptotic behavior of an upper bound is studied. Finally, the asymptotic behavior of the Markov–Bernstein constant is O ( n 2 ) in both cases.